Partnering Higher Education and K–12 Institutions in OER: Foundations in Supporting Teacher OER-Enabled Pedagogy - Arispe, Kelly; Hoye, Amber (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
Open educational resources (OER) are disproportionately created and/or accessed by institutions of higher education as compared to K–12 even though teachers confront the challenge of outdated teaching materials or, worse, an increasing trend by school districts to discontinue textbook adoption altogether. In this paper, we describe a sustainable and innovative example of OER-enabled pedagogy (OEP) that partners teachers and students across institutional boundaries to address these problems. The Pathways Project (PP) is a higher education and K–12 community of 350 world-language teachers, students, and staff that engage in the 5Rs (retain, reuse, revise, remix, and redistribute) of OEP with a repository of more than 800 OER ancillary activities that support standards-based pedagogy for 10 world languages and cultures. The PP is innovative because it fosters renewable assignments for the entire disciplinary ecosystem unlike most OEP studies that discuss renewable assignments limited to a single course. Teacher education is one of the best places to engage OEP because teachers are trained to personalize and contextualize OER materials for their local classroom needs. In so doing, the PP community receives timely discipline-specific professional development that is in high demand, especially in rural communities where teachers are isolated. Higher education-K–12 OEP partnerships are rare, and yet teacher education programs exist in most universities and can be a logical place to start. This paper provides concrete examples and practical steps that are transferable to other disciplines looking to engage in similar types of OER-OEP collaboration and community engagement.